Diseño de un sistema de adquisiciones estratégicas para una empresa farmacéutica que ayude a alcanzar los objetivos estratégicos de la compañia - León Cisneros, Daniela (2014)
The following study is qualitative descriptive and explanatory applied to a particular case on a local pharmaceutical company. The study is based on the theory of integrative contingency. This theory is based on the fact that external environment affects the structure and efficiency of enterprises, therefore, is of great importance to know how to balance the environment and internal process and organizational culture in order to achieve high levels of performance. The model suggested, strategic sourcing, is coupled to the context and environment of the company. Additionally, opportunities for improvement, maximizing purchasing power, maximizing efficiency and growth are identified... See attached file